UNIVERSAL PRECAUTION OF SECTIO CAESARIA IN SURGICAL ROOM - Anindita Santoso; Prastuti Soewondo (Proceedings of the International Conference on Applied Science and Health, 2019)
Background:Nosocomial infection is the presence of an infection seen in patients while in the hospital or while in other health facilities, currently this is are known as Health-care Associated Infections (HAI). One of useful strategy in controlling HAI is to improve the ability of health workers in the universal precautions method. To succeed in this strategy, we need a material briefing on universal precautions so that good knowledge is obtained between healthcare staff. Therefore it is necessary to know the relationship between knowledge about universal precautions with universal precautions attitude and safety skills on healthcare staff. Methods:Article research was limited to articles from internet databases, such as ASMR, Elsevier Journal, IJCMPH, Sage Journals with the keywords universal precaution, knowledge, safety skills, attitude, and healthcare staff. Inclusion criteria, such as English articles and published from 2008- 2018,were collected and reviewed. The searching process obtained 6 articles that met requirement for inclusion and exclusion criteria. Results: There were two articles that found positive correlation between knowledge of universal precautions and safety skills or attitude, but the others showed otherwise. It shows inconsistent findings in all articles. Conclusions:Knowledge of universal precaution is not the only factor that influences the safety skills or attitude of healthcare staff. It might be other factors that influence safety skill or attitude beside knowledge of universal precaution.